Analysis of wideband tympanometry in Ménière’s disease - Tanno,Gisela Andrea Yamashita (2022)
Abstract Introduction: Endolymphatic hydrops is the pathophysiological substrate of Ménière’s disease. The changes in the inner ear, transmitted to the middle ear through changes in the ossicular chain mobility, can be quantified by wideband tympanometry, through the measurement of the acoustic absorbance at multiple frequencies, represented by the sound energy absorbed by the middle ear, even at its early stages. Studying the behavior of the middle ear through the absorbance in patients with endolymphatic hydrops under ambient pressure and under peak pressure can be useful for detecting Ménière’s disease. Objective: To characterize acoustic absorbance behavior in subjects with symptomatic and asymptomatic Ménière’s disease compared to controls, in order to verify the ability of wideband tympanometry to detect Ménière’s disease. Methods: We carried out a cross-sectional study with a diagnostic approach comparing the findings of wideband tympanometry at ambient pressure and peak pressure between the ears of the control group (n = 30), the asymptomatic group (n = 21) and the symptomatic group (n = 9). Results: Different peak pressure values were found between the ears of the control group (0daPa), the asymptomatic group (−11 daPa) and the symptomatic group (−192 daPa), with p < 0.05 by the Kruskal-Wallis test, Mann Whitney test and Bonferroni correction. Different absorbance values were found between the ears of the symptomatic group and the asymptomatic group compared to the control group for low frequencies at ambient pressure and peak pressure, with p < 0.05 by the Kruskal-Wallis test, Mann Whitney test and Bonferroni correction. Conclusions: The Wideband Tympanometry test was capable of identifying the presence of Ménières disease, and to differentiate between asymptomatic and symptomatic patients, when comparing them with healthy individuals.